2022
DOI: 10.1007/s00384-022-04206-7
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of rectovaginal fistula—predictors of outcome and effects on quality of life

Abstract: Purpose To determine the results after rectovaginal fistula (RVF) repair and find predictors of outcome. Primary objective was fistula healing. Secondary outcomes were morbidity and patient health-related quality of life (HRQoL). Method An observational study of 55 women who underwent RVF repair including both local procedures and tissue transposition 2003–2018 was performed. Baseline patient and fistula characteristics were registered, combined with a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Surgery volume, type and geographical distribution Fistula Foundation supported a total of 24 568 surgeries between 2019 and 2021. The fistula surgeries funded during this period included treatment for vesicovaginal fistula (VVF; an abnormal opening between the bladder and vagina 12 ), rectovaginal fistula (RVF; an abnormal opening between the rectum or anus and vagina 13 ), ureteric fistula (a hole between the ureter and vagina 14 ) and urethral fistula (a hole between the urethra and vagina 15 ). Additionally, Fistula Foundation supported related procedures for women with a history of fistula including sling and urethroplasty, vaginoplasty, urinary diversion, bladder stone removal, catheterisation, colostomy opening and closing, and examinations under anaesthesia (EUA).…”
Section: Resultsmentioning
confidence: 99%
“…Surgery volume, type and geographical distribution Fistula Foundation supported a total of 24 568 surgeries between 2019 and 2021. The fistula surgeries funded during this period included treatment for vesicovaginal fistula (VVF; an abnormal opening between the bladder and vagina 12 ), rectovaginal fistula (RVF; an abnormal opening between the rectum or anus and vagina 13 ), ureteric fistula (a hole between the ureter and vagina 14 ) and urethral fistula (a hole between the urethra and vagina 15 ). Additionally, Fistula Foundation supported related procedures for women with a history of fistula including sling and urethroplasty, vaginoplasty, urinary diversion, bladder stone removal, catheterisation, colostomy opening and closing, and examinations under anaesthesia (EUA).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in the study, patients with fistulas had a decreased quality of life-in the social and sports domains [9]. Söderqvist et al showed that patients with an unhealed fistula had lower scores in 6 out of 8 domains of the Health-Related Quality of Life questionnaire than both healed patients and the normal population [3]. Secondly, sexual dysfunctions occur.…”
Section: Introductionmentioning
confidence: 81%
“…Depending on statistics, the healing rates of surgery in RVF range from 20 to 100% [1], which is still not satisfying. The authors of the studies regarding the main cause of unsatisfactory treatment results see the presence of persistent inflammation, which triggers a prolonged wound healing and as a consequence the excessive deposition of extracellular matrix further hindering recovery [2,3]. Therefore, the frequency of RVF recurrences is high and ranges from 20% to even 90% [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the chosen treatment modality, the failure rate associated with RVF repair remains high. Numerous authors have reported a success rate of only 55%–60% for initial procedures, while others have reported even lower rates of 25% ( 7 , 10 ). However, with subsequent procedures, the overall success rate improves to approximately 70%–90%.…”
Section: Discussionmentioning
confidence: 99%
“…However, the classification of RVFs into simple and complex types based on factors such as size, location, etiology, and their relationship to the anal sphincter complex can guide treatment decisions ( 11 , 12 ). Simple fistulas, typically smaller and more distally located, often result from trauma or infection and they are associated with better prognosis, while complex fistulas are associated with more severe conditions like inflammatory bowel disease, invasive cancer or radiation ( 10 , 12 ).…”
Section: Discussionmentioning
confidence: 99%